The fallacy of one-dimensional theory of planned behaviour structure in predicting health behaviour - Wee Yu Ghee; Yap Sheau-Fen; Md Nor Othman (2013)
Most research on exercise is dominated in the West. Drawing on a socio-cognitive theory, this research aims at addressing methodological issues in an Eastern culture where recent developments of the theory of planned behaviour (TPB) applications have been limited. To answer the call for reinterpretation of the TPB measurement, we propose and test a more complex factor structure of TPB predictors. Cross-sectional data was collected from a quota sample of 512 adults in Malaysia. This study provides an empirical validation that the multidimensional, first-order model has achieved measurement validity and possesses better fit compared to the global, second-order TPB structure. Our investigation of the specific effects of social cognitive components on exercise intention and behaviour also improves the understanding of this theoretical relationship.